1995
DOI: 10.1016/0550-3213(95)00205-7
|View full text |Cite
|
Sign up to set email alerts
|

Charged dilaton black holes with unusual asymptotics

Abstract: We present a new class of black hole solutions in Einstein-Maxwell-dilaton gravity in n ≥ 4 dimensions. These solutions have regular horizons and a singularity only at the origin. Their asymptotic behavior is neither asymptotically flat nor (anti-) de Sitter.Similar solutions exist for certain Liouville-type potentials for the dilaton.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
351
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(369 citation statements)
references
References 26 publications
17
351
1
Order By: Relevance
“…This solution is distinct from the two-exponential, neutral solution first reported in [33], whose single exponential, planar version (3.7) is shown in section 4.1 to uplift to the planar Schwarzschild-AdS black hole for δ < δ c .…”
Section: Jhep12(2011)036contrasting
confidence: 56%
See 1 more Smart Citation
“…This solution is distinct from the two-exponential, neutral solution first reported in [33], whose single exponential, planar version (3.7) is shown in section 4.1 to uplift to the planar Schwarzschild-AdS black hole for δ < δ c .…”
Section: Jhep12(2011)036contrasting
confidence: 56%
“…Early studies of the black-hole solutions of such actions may be found in [33][34][35], while they were later revisited systematically in [32]. In the domain-wall coordinate system,…”
Section: Jhep12(2011)036mentioning
confidence: 99%
“…In presence of the higher order corrections the term "Einstein frame" is ambiguous for the scalar and tensor parts mix inevitably through the higher order terms. Forα r = 0, our solution (2.24) is a generalisation of that of [79]. Settingκ = 0 in (2.23) brings us back to the case of a toroidal reduction and to the planar dilatonic black hole of section 2.2.…”
Section: Jhep09(2012)011mentioning
confidence: 91%
“…To study further the dynamics when couplings (such as the 't Hooft coupling) are large but finite, higherderivative interactions must be included. Indeed, these will become important close to the singularity for the electrically charged solutions as the scalar runs logarithmically and the string coupling diverges, [61,64,79] (in the magnetic case on the other hand, quantum effects will need to be taken into account, [69,70]). Moreover, transport coefficients such as the shear viscosity, which control the out-of-equilibrium behaviour and obey universal laws in two-derivative setups, [71], may violate these laws upon turning on higher derivatives, [5].…”
Section: Jhep09(2012)011mentioning
confidence: 99%
See 1 more Smart Citation